Training health providers to address unhealthy alcohol use in primary care: a cross-sectional, multicenter study - Esperanza Romero-Rodríguez; Luis Ángel Pérula de Torres; Roger Ruiz Moral; José Ángel Fernández García; Juan Manuel Parras Rejano; Ana Roldán Villalobos; Francisco Camarelles Guillem; Collaborative Group Alco-AP (BMC, 2020)
Abstract Background Health professionals' training is a key element to address unhealthy alcohol use in Primary Care (PC). Education about alcohol use can be effective in improving PC provider's knowledge and skills addressing alcohol-related problems. The aim of the study was to evaluate the training of health professionals to address unhealthy alcohol use in PC. Methods An observational, descriptive, cross-sectional, multicenter study was performed. Location: PC centres of the Spanish National Health System (SNHS). Participants: Family physicians, residents and nurses completed an online questionnaire that inquired about their training (none, basic, medium or advanced), knowledge and preventive practices aimed at reducing unhealthy alcohol use. The study population was recruited via random sampling, stratified by the regions of the SNHS's PC centre, and by email invitation to members of two Spanish scientific societies of Family Medicine. Results A total of 1760 professionals participated in the study. Sixty-seven percent (95% CI: 67.5-71.8) reported not having received specific training to address unhealthy alcohol use, 30% (95% CI: 27.4-31.7) reported having received basic training, and 3% (95% CI: 2.3-4.0) medium/advanced training. The training received was greater in younger providers (p < 0.001) who participated in the PAPPS (Preventive Activities and Health Promotion Programme) (p < 0.001). Higher percentages of providers with intermediate or advanced training reported performing screening for unhealthy alcohol use (p < 0.001), clinical assessment of alcohol consumption (p < 0.001), counselling of patients to reduce their alcohol intake (p < 0.001) or to abstain, in the cases of pregnant women and drivers (p < 0.001). Conclusion Our study reveals a low level of training among Spanish PC providers to address unhealthy alcohol use. A higher percentage of screening, clinical assessment and counselling interventions aimed at reducing unhealthy alcohol use was reported by health professionals with an intermediate or advanced level of training.